2022
DOI: 10.3389/fcell.2022.842285
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Vps13 is Crucial for Peroxisome Expansion in Cells With Reduced Peroxisome-ER Contact Sites

Abstract: In the yeast Hansenula polymorpha the peroxisomal membrane protein Pex11 and three endoplasmic reticulum localized proteins of the Pex23 family (Pex23, Pex24 and Pex32) are involved in the formation of peroxisome-ER contact sites. Previous studies suggested that these contacts are involved in non-vesicular lipid transfer and important for expansion of the peroxisomal membrane. The absence of Pex32 results in a severe peroxisomal phenotype, while cells lacking Pex11, Pex23 or Pex24 show milder defects and still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…Artificial targeting of Pex3 to mitochondria is compatible with peroxisome biogenesis in S. cerevisiae and provokes tethering of peroxisomes to this organelle [60]. Protein trafficking via a vesicular carrier [40,[61][62][63][64][65][66] or direct membrane flow [24,25,[67][68][69][70] accompanied by protein transit at contact sites may be parallel processes and may both depend on dual affinity proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial targeting of Pex3 to mitochondria is compatible with peroxisome biogenesis in S. cerevisiae and provokes tethering of peroxisomes to this organelle [60]. Protein trafficking via a vesicular carrier [40,[61][62][63][64][65][66] or direct membrane flow [24,25,[67][68][69][70] accompanied by protein transit at contact sites may be parallel processes and may both depend on dual affinity proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same domains may be required for the budding of peroxisome precursors ( Joshi et al, 2016 ; Joshi et al, 2018 ; Wang et al, 2018 ). As an alternative to vesicle formation, direct lipid transfer promotes the growth of peroxisomes and recruitment of lipid transfer proteins such as VPS13 is involved in peroxisome biogenesis both in yeasts and in mammals ( Raychaudhuri and Prinz, 2008 ; Baldwin et al, 2021 ; Guillén-Samander et al, 2021 ; Yuan et al, 2022 ). How these mechanisms for lipid supply each contribute to peroxisome formation is an exciting question for future work.…”
Section: Proteins Localized To Peroxisomes and The Endoplasmic Reticulummentioning
confidence: 99%
“…Why peroxisome numbers are decreased in cells lacking Pex23 family proteins is still unknown. Intriguingly, H. polymorpha pex23 and pex24 cells have very similar peroxisome abnormalities as H. polymorpha pex11 cells, namely reduced peroxisome abundance together with an increase in organellar size ( Krikken et al, 2009 ; Yuan et al, 2022 ). Like in pex23, pex24, and pex32 cells, also in pex11 cells, peroxisome-ER contact sites are disrupted ( Wu et al, 2020 ), suggesting that Pex23 family proteins at ER together with Pex11 at the peroxisomal membrane are involved in peroxisome-ER contact site formation.…”
Section: Introductionmentioning
confidence: 97%
“…We recently showed that H. polymorpha Pex23, Pex24, and Pex32, but not Pex29, play important roles in the formation of ER-peroxisome contact sites ( Wu et al, 2020 ). In the absence of HpPex23, HpPex24, or HpPex32, fewer peroxisome-ER contact sites occur, paralleled by a reduction in the average peroxisomal membrane surface and decreased peroxisome numbers ( Wu et al, 2020 ; Yuan et al, 2022 ). The reduction in peroxisomal membrane surface suggests that contact sites may play a role in the transfer of lipids from ER to peroxisomes to allow organellar expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation